A prescription guide for baclofen in Alcohol Use Disorder- For use by physicians and patients - Sylvie Imbert; Samuel Blaise; Jacques Bérard; Renaud de Beaurepaire; Amanda Stafford; Philippe Jaury (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2017)
Since the discovery by Olivier Ameisen that high-dose baclofen can produce a state of indifference towards alcohol in those with Alcohol Use Disorders (AUD), the prescription of baclofen in AUD patients has exponentially increased. There are currently hundreds of thousands of patients with AUD who benefit from this treatment in France. However, the prescription of baclofen is difficult in many ways. First, the treatment, which consists in a slow progressive increase of doses, must be individually adapted, some patients needing low doses to achieve a state of indifference, while others need high or very high doses. Second, baclofen produces many adverse effects that can be very uncomfortable for patients, and may sometimes be dangerous. The third is that the patients must be strongly engaged in the management of the treatment, as they are the ones who will have to find the best way to target the moments of cravings and determine the distribution of the doses over the day to limit the occurrence of adverse effects. The doctor: patient therapeutic alliance is therefore a crucial element in the management of baclofen treatment. The present article is a guide written by both doctors and cured patients ("expert patients") for the prescription of baclofen in AUD.